2018
DOI: 10.3390/agronomy8050065
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rice Straw and Biochar Applications on the Microbial Community in a Soil with a History of Continuous Tomato Planting History

Abstract: Soil microbial abundance and diversity change constantly in continuous cropping systems, resulting in the prevalence of soil-borne pathogens and a decline in crop yield in solar greenhouses. To investigate the effects of rice straw and biochar on soil microbial abundance and diversity in soils with a history of continuous planting, three treatments were examined: mixed rice straw and biochar addition (RC), rice straw addition (R), and biochar addition (C). The amount of C added in each treatment group was 3.78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
0
15
0
2
Order By: Relevance
“…It has been reported that straw incorporation has significant beneficial effects on crop yields and soil properties. For instance, straw incorporation can increase crop yields [16,17], soil organic matter [10,[17][18][19], and other soil nutrients [10,18,20]. Straw return can also improve soil physical properties, such as by increasing hydraulic conductivity, decreasing bulk density, and enhancing aggregate formation [16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that straw incorporation has significant beneficial effects on crop yields and soil properties. For instance, straw incorporation can increase crop yields [16,17], soil organic matter [10,[17][18][19], and other soil nutrients [10,18,20]. Straw return can also improve soil physical properties, such as by increasing hydraulic conductivity, decreasing bulk density, and enhancing aggregate formation [16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Pemberian sianobakteria meningkatkan status K tersedia dari sangat rendah menjadi tersedia rendah. Zhang et al (2018) melaporkan bahwa penggunaan bahan organik yang cukup berdampak pada kenaikan pH tanah, fosfat tersedia, nitrogen tersedia, dan kalium tersedia dalam tanah.…”
Section: Sifat Kimia Tanahunclassified
“…Aplikasi biochar pada media pertumbuhan meningkatkan kesuburan tanah (Hamzah & Shuhaimi, 2018), (Krishnakumar et al, 2014), (Videgain-Marco et al, 2020). Biochar dari sekam padi dan jerami dapat menghemat biaya kapur, pupuk, emisi gas rumah kaca terutama di lahan kritis (Jeffery et al, 2017), (Zhang et al, 2018).Studi terbaru menunjukkan bahwa biochar dan kapur dapat efektif untuk meningkatkan sifat fisikokimia tanah merah dan hasil gandum (Malik et al, 2018). Dengan demikian biochar memiliki manfaat yang sangat besar dan luas, terutama dalam memperbaiki kondisi lahan kritis agar menjadi lahan produktif.…”
Section: Pendahuluanunclassified